2014
DOI: 10.5812/ircmj.15472
|View full text |Cite
|
Sign up to set email alerts
|

Financial Management Reforms in the Health Sector: A Comparative Study Between Cash-based and Accrual-based Accounting Systems

Abstract: Background:Financial management and accounting reform in the public sectors was started in 2000. Moving from cash-based to accrual-based is considered as the key component of these reforms and adjustments in the public sector. Performing this reform in the health system is a part of a bigger reform under the new public management.Objectives:The current study aimed to analyze the movement from cash-based to accrual-based accounting in the health sector in Iran.Patients and Methods:This comparative study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The variables for the comparison were extracted from a review of the literature and included the following: legal framework, legal scope, health sector, policy framework, structural framework, contract framework, and funding procedure (16,17). These variables were validated by the research team and two more experts in the area of PPP.…”
Section: Methodsmentioning
confidence: 99%
“…The variables for the comparison were extracted from a review of the literature and included the following: legal framework, legal scope, health sector, policy framework, structural framework, contract framework, and funding procedure (16,17). These variables were validated by the research team and two more experts in the area of PPP.…”
Section: Methodsmentioning
confidence: 99%
“…HTP was implemented in May 5, 2014, with 8 service packages (6). The main factors of the reform, which was introduced by experts in the health system are as follows: increasing health care costs, increasing public expectations, resources limitation and increasing public demand from the government due to poor governance, corruption and inefficiency of power, and bureaucratic inhibitors (8,9). Three financial sources are determined for supporting the plan: increasing the public annual budget of health sector, resources of the targeted subsidies' law (10% of total subsidies), and a specific 1% value added tax (VAT) for health.…”
Section: Introductionmentioning
confidence: 99%
“…Health systems not only play a critical and important role in improving health, but also are responsible to protect individuals against the financial costs of illnesses and diseases ( 13 ). Regarding the fact that financial management is one of the basic principles in the health sector, providing and managing financial resources is critical ( 14 ). Studies have shown increases in hospitalization costs during the first year of life for the infants suffering from some early defects such as bronchopulmonary dysplasia and intraventricular hemorrhage ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%